Gesù e il sacrificio ebraico - Pesce, Mauro (Annali di storia dell'esegesi, 2001)
In Matt. 6,12 God's forgiveness is obtained through a trilateral relationship between the sinner, the ‘debtor’, and God, without any expiatory sacrificial act, without any kind of bodily humiliation, or bodily decontamination, and without Jesus having any function. Jesus did not, however, reject the sacrificial rituals of the temple, which did not serve to expiate voluntary sins. This is shown by an analysis of Mark 1,40-44.45 (// Matt. 8,1-4; Luke 5,12-14.15; PEger 2) and Matt. 5,23-24;9,13;12,7.